2017
DOI: 10.1177/8755122516686226
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laws Regulating Pain Clinics on Opioid Prescribing and Opioid-Related Toxicity Among Texas Medicare Part D Beneficiaries

Abstract: Background Pain management clinics are major sources of prescription opioids. Texas government passed several laws regulating pain clinics between 2009 and 2011 to reduce opioid-related toxicity. Understanding the impact of these laws can inform policy geared toward making the laws more effective in curbing the growing epidemic of opioid overdose, especially among the elderly population. Objectives To examine the longitudinal association of laws regulating pain clinics on opioid-prescribing and opioid-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…After controlling for those county characteristics, the presidential vote explained 7% of the variation in opioid use. Model 3 adds variables describing the degree of state regulations on opioid prescribing 22 , 23 , 24 ; in this model the presidential vote still explains 6% of the county-level variation. The model R 2 was 0.44 for model 2 and 0.46 for model 3, indicating that the variables included explained 44% and 46% of the variance in county opioid rates, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After controlling for those county characteristics, the presidential vote explained 7% of the variation in opioid use. Model 3 adds variables describing the degree of state regulations on opioid prescribing 22 , 23 , 24 ; in this model the presidential vote still explains 6% of the county-level variation. The model R 2 was 0.44 for model 2 and 0.46 for model 3, indicating that the variables included explained 44% and 46% of the variance in county opioid rates, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The second model adjusted for county demographic characteristics and the third model added whether the state had any of 7 categories of laws regulating opioid prescribing. 22 , 23 , 24 The parameter estimate and partial R 2 for each characteristic were reported. All tests of statistical significance were 2-sided with significance set at P < .05, and analyses were performed with SAS Enterprise statistical software version 7.12 at the CMS Virtual Research Data Center (SAS Institute Inc).…”
Section: Methodsmentioning
confidence: 99%
“…2,3 We recently published our analysis of the relationship between Texas 2009-2011 laws regulating pain management clinics and the use and toxicity of prescription opioids in Medicare beneficiaries. 4 We did not find any association between the laws and the monthly percentages of Medicare patients hospitalized for opioid toxicity. We recently received an update of the 2010 Texas Medicare Beneficiary data from the Research Data Assistance Center, which allowed us to recalculate the rate of acute hospitalization for opioid toxicity using a more specific definition of potential opioid-related overdose, as used by Dunn et al, 5 to identify acute hospitalization related to potential overdose.…”
mentioning
confidence: 55%
“…68 However, a morerecentstudyonGoodSamaritanlawsfoundnosignificanteffectonopioid-relatedoverdosemortality. 102 Similarly, studies on pill-mill laws that we reviewed found an increase in the number of opioid prescriptions in Texas 58,59 and opioid-related mortality in Florida 57 ; however, a 2019 study foundnulleffectsofpill-milllawsonopioidprescriptionsin Ohio and Tennessee, despite robust enforcement of these laws. 103 Two additional studies in 2019 on medical marijuana policies found lower rates of opioid use in areas with legalized medical marijuana policy than in areas without such policy, consistent with our results.…”
Section: Discussionmentioning
confidence: 93%
“…Pill-mill laws in Texas were associated with reduced opioid use (number of prescriptions, average daily MME doses, and number of pills dispensed) 58 ; however, they were not associated with changes in the monthly percentageofMedicarebeneficiarieswhofilledScheduleII or Schedule III prescriptions or with rates of opioid-related hospitalizations. 59 Pain clinic regulations and increased penalties for overprescribing were associated with fewer prescription opioid and heroin overdose deaths in Florida compared with North Carolina, which did not have pain clinic regulations. 57 Medical and recreational marijuana policy.…”
Section: Benefit Databasementioning
confidence: 94%